The Influence of Smartphone Text Input Method, Posture, and Environment on User Experience - Li, Ying; You, Fangzhou; Ji, Ming; You, Xuqun (International journal of human-computer interaction, 2020)
Text input on smartphones plays an increasingly important role in people's daily lives. This study aims to explore the impact of posture and environment on the user experience of smartphone input methods. A combination of performance, subjective, and physiological measures is used to assess the user experience of 32 subjects (12 male, 20 female; 18-26 years old) using QWERTY and T9 input methods in walking and sitting postures in indoor and outdoor environments. The results showed that T9 was more effective for indoors and when sitting than QWERTY, while QWERTY was more effective than T9 for outdoors and when walking. In our tests, using T9 indoors while sitting showed a significantly higher performance than QWERTY, while using QWERTY outdoors while walking elicited significantly lower emotional arousal than T9. The findings allow us to propose both the optimal contexts in which to use particular input methods, and to highlight new approaches for improving the user experience of these devices.